Datowanie radiowęglowe grobów komorowych z wczesnośredniowiecznego cmentarzyska w Sowinkach (stan. 23a) w Wielkopolsce - Krzyszowski, Andrzej; Błaszczyk, Dariusz (Folia Praehistorica Posnaniensia, 2016)
This paper presents and discusses the results of 14C dating of two chamber graves (no. 148 and 151) from the early medieval cemetery at Sowinki, site 23A (Wielkopolska).